Seed dormancy responses to temperature relate to Nothofagus species distribution and determine temporal patterns of germination across altitudes in Patagonia - Arana, María Verónica; Gonzalez Polo, Marina; Martinez Meier, Alejandro; Gallo, Leonardo Ariel; Benech-Arnold, Roberto Luis; Sanchez, Rodolfo Augusto; Batlla, Diego (2017)
Seeds integrate environmental cues that modulate their dormancy and germination. Although many mechanisms have been identified in laboratory experiments, their contribution to germination dynamics in existing communities and their involvement in defining species habitats remain elusive. By coupling mathematical models with ecological data we investigated the contribution of seed temperature responses to the dynamics of germination of three Nothofagus species that are sharply distributed across different altitudes in the Patagonian Andes. Seed responsiveness to temperature of the three Nothofagus species was linked to the thermal characteristics of their preferred ecological niche. In their natural distribution range, there was overlap in the timing of germination of the species, which was restricted to mid-spring. By contrast, outside their species distribution range, germination was temporally uncoupled with altitude. This phenomenon was described mathematically by the interplay between interspecific differences in seed population thermal parameters and the range in soil thermic environments across different altitudes. The observed interspecific variations in seed responsiveness to temperature and its environmental regulation, constitute a major determinant of the dynamics of Nothofagus germination across elevations. This phenomenon likely contributes to the maintenance of patterns of species abundance across altitude by placing germinated seeds in a favorable environment for plant growth.